2020
DOI: 10.3390/microorganisms8101532
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Diagnostic Fumarate Addition Metabolites and Genes Provides Evidence for Anaerobic Hydrocarbon Biodegradation in Contaminated Groundwater

Abstract: The widespread use of hydrocarbon-based fuels has led to the contamination of many natural environments due to accidental spills or leaks. While anaerobic microorganisms indigenous to many fuel-contaminated groundwater sites can play a role in site remediation (e.g., monitored natural attenuation, MNA) via hydrocarbon biodegradation, multiple lines of evidence in support of such bioremediation are required. In this study, we investigated two fuel-contaminated groundwater sites for their potential to be managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Although the results show some general trends in redox conditions at the site, the results also demonstrate a large level of variability and therefore unpredictability of subsurface conditions at the Griftpark. Similar variations at a single site were documented by Kharey et al at two fuel-contaminated groundwater sites [155]. They found that nitrate, sulphate and iron reduction occurred with varying levels of potential at different locations of the sites, making it challenging to discern clear trends between hydrocarbon concentrations with the electron accepting processes.…”
Section: Electron Acceptorssupporting
confidence: 74%
“…Although the results show some general trends in redox conditions at the site, the results also demonstrate a large level of variability and therefore unpredictability of subsurface conditions at the Griftpark. Similar variations at a single site were documented by Kharey et al at two fuel-contaminated groundwater sites [155]. They found that nitrate, sulphate and iron reduction occurred with varying levels of potential at different locations of the sites, making it challenging to discern clear trends between hydrocarbon concentrations with the electron accepting processes.…”
Section: Electron Acceptorssupporting
confidence: 74%
“…No nitrate, nitrite, organic acids (such as acetate) or aromatic hydrocarbons were detected in these samples. However, previous groundwater analyses (in 2016) indicated that benzene and toluene levels in this site reached 8.39 mg/L and 0.377 mg/L [ 33 ], both exceeding Canadian maximum allowable concentrations (0.005 and 0.024 mg/L, respectively [ 34 ]). The lack of hydrocarbons detected in the present groundwater samples was likely due to volatilization that occurred during transportation and storage.…”
Section: Methodsmentioning
confidence: 84%
“…In contrast, microbial communities incubated anoxically failed to oxidize any benzene over 80 days of monitoring ( Figure S3 ). Given the levels of benzene detected at the Stony Plain site in 2016 (8.39 mg/L [ 33 ]), we hypothesized that anaerobic benzene degradation would occur due to its historical exposure to the indigenous microbial population. However, this was not realized within the 80 day incubation period across the anaerobic conditions tested.…”
Section: Resultsmentioning
confidence: 99%
“…MI performed qPCR utilizing commercially available assays for bssA, assA, mnssA, bcrA, ANC, and APS. It is important to note that some of the commercially available assays involve the use of multiple qPCR assays (five assays for bssA, six for assA, two for mnssA, three for bcrA, and seven for APS) for which quantities are added as previously described (Beller et al, 2002;Rossmassler et al, 2019;Kharey et al, 2020).…”
Section: Sampling and Analysis Of Mbtsmentioning
confidence: 99%